THE DEVELOPMENT OF A TREFFINGER MODEL BASED ON HYBRID LEARNING ON THE BHINEKA TUNGGAL IKA (PPSPS) THEME FOR THE FOURTH GRADE OF ELEMENTARY SCHOOL - Irmaningrum, Rizka Novi; Zativalen, Oriza; Nurhidayat, M. Arif (UIN Sunan Kalijaga Yogyakarta, 2023)
The objective of this research is to develop a learning model in the Project of Pancasila Student Profile Strengthening (PPSPS). This model is a Treffinger model based on hybrid learning for elementary school students. The development of a Treffinger model based on hybrid learning in this research used a development model adapted from Plomp (1997). The development model by Plomp has five main stages, including (1) preliminary investigation, (2) design, (3) realization/construction, (4) test, evaluation, and revision, and (5) implementation. The subjects of this research were the students in class 4A and 4B of Muhammadiyah Elementary School (MES) 1 Babat. The instruments used were student learning outcomes and student responses to the learning process. The validation instruments in this research were the validation tests of the lesson plans/teaching modules, students worksheets, student books, model books, and assessment instruments. Based on the results of preliminary study, a hybrid-learning-based Treffinger model was designed. The model design in this study included (1) model book design, (2) design of learning components (student books, teaching modules, worksheets), and (3) instrument design to obtain data in the model development process. The development of the Treffinger model based on hybrid learning was tested for the validity, resulting in a percentage of 92%, whereas the effectiveness was tested based on teacher observations resulting in a percentage of 93%. The learning outcomes had a percentage of 83%, and the practicality test based on student responses resulted in a percentage of 97%. Based on these research results, the development of the Treffinger Model based on hybrid learning is considered suitable for use.